A Ratiometric Fluorescence Imaging System for Surgical Guidance. (16th October 2008) - Moriyama, Eduardo H.; Kim, Anthony; Bogaards, Arjen; Lilge, Lothar; Wilson, Brian C.
Abstract : A 3-chip CCD imaging system has been developed for quantitative in vivo fluorescence imaging. This incorporates a ratiometric algorithm to correct for the effects of tissue optical absorption and scattering, imaging "geometry" and tissue autofluorescence background. The performance was characterized, and the algorithm was validated in tissue-simulating optical phantoms for quantitative measurement of the fluorescent molecule protoporphyrin IX (PpIX). The technical feasibility to use this system for fluorescence-guided surgical resection of malignant brain tumor tissue was assessed in an animal model in which PpIX was induced exogenously in the tumor cells by systemic administration of aminolevulinic acid (ALA).